(untitled) (Research, Society and Development, 2021)
This article aims to analyze the production of materials in Libras about the coronavirus during the pandemic. This is an explanatory and quantitative review carried out from March to early September 2020. The searches were carried out in institutions in Brazil, mainly universities. The results showed that federal universities accounted for 63.82% production. Bilingual material was made available on different social media, namely: YouTube (38.29%), University Websites (25.53%), Facebook and Instagram (19.14%) and others (17.02%). 53.84% of the productions were published by state universities in the south region and 30.76% in the southeast region. In federal universities, 66.66% of the findings represented the south/southeast regions and 16.66% the central-west region. From this study, it was found that only a limited number of materials were produced in Libras about the new coronavirus, and little dissemination of existing materials. Thus, it was considered essential to incorporate instruments that ensure that this population is served in an equitable manner.